1998
DOI: 10.1111/1468-5957.00195
|View full text |Cite
|
Sign up to set email alerts
|

Market Reactions to the Hong Kong Trading Suspensions: Mandatory versus Voluntary

Abstract: This paper investigates the market reactions to regulator-initiated (mandatory) suspension and issuer-initiated (voluntary) suspension on the Stock Exchange of Hong Kong. It is found that there is substantial devaluation of the stocks during either suspension, and both the variance and trading volume are higher in the post-suspension period than in the pre-suspension period. However, the changes in value and variance are sensitive to the reason for the suspension. The evidence shows that mandatory suspensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
6
23
1
Order By: Relevance
“…Second, a trading suspension is either ordered by a regulatory body or requested by a listed company; these issuer-initiated suspensions make up more than 90% of all trading suspensions in Hong Kong. Wu (1998) finds that variance and trading volume are higher in the post-suspension period than in the presuspension period on the SEHK, which suggests that suspensions do not immediately ease unusual volatility or trading activity. Kryzanowski and Nemiroff (1998) investigate the price discovery process around trading halts on the Montreal Exchange using trade-by-trade data and find that volatility and trading activity increase significantly around trading halts but return to lower levels less than two days after the resumption of trading.…”
Section: Exchange Trading Haltsmentioning
confidence: 97%
See 2 more Smart Citations
“…Second, a trading suspension is either ordered by a regulatory body or requested by a listed company; these issuer-initiated suspensions make up more than 90% of all trading suspensions in Hong Kong. Wu (1998) finds that variance and trading volume are higher in the post-suspension period than in the presuspension period on the SEHK, which suggests that suspensions do not immediately ease unusual volatility or trading activity. Kryzanowski and Nemiroff (1998) investigate the price discovery process around trading halts on the Montreal Exchange using trade-by-trade data and find that volatility and trading activity increase significantly around trading halts but return to lower levels less than two days after the resumption of trading.…”
Section: Exchange Trading Haltsmentioning
confidence: 97%
“…Second, a trading suspension is either ordered by a regulatory body or requested by a listed company; these issuer‐initiated suspensions make up more than 90% of all trading suspensions in Hong Kong. Wu (1998) finds that variance and trading volume are higher in the post‐suspension period than in the pre‐suspension period on the SEHK, which suggests that suspensions do not immediately ease unusual volatility or trading activity.…”
Section: Firm‐specific Trading Haltsmentioning
confidence: 97%
See 1 more Smart Citation
“…They observed that both the price variance and trading volume are substantially higher than normal in the immediate pre-suspension period, and this trend continues in the immediate post-suspension period. Using data from Hong Kong, Wu (1998) finds that there are significant negative returns during either regulator-initiated trading suspensions or issuer-initiated trading suspensions from the stock exchange, and both the price variance and trading volume are higher in the post-suspension period than in the pre-suspension period. However, mandatory suspensions are more effective than voluntary suspensions in disseminating information.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In Montreal Stock Exchange, Kryzanowski and Nemiroff () find evidence of significant volatility spillover. In Hong Kong, Wu () compares mandatory versus discretionary suspension mechanisms and finds volatility to be higher for mandatory halts. The same was found in Singapore Stock Exchange by Tan and Yeo (), who further reported elevated volatility after both good and bad news suspensions.…”
Section: Empirical Workmentioning
confidence: 99%